(untitled) (EU and comparative law issues and challenges series (ECLIC), 2023)
Contemporary armed conflict has witnessed an increased employment of digital technologies in the conduct of hostilities. While there is broad consensus on the full applicability of the rules and principles of international humanitarian law (IHL) to the “fifth domain” of warfare, many issues remain debated. More specifically, digital technologies allow a wide range of actors other than States – such as individuals, “hacktivists”, criminal groups, non-State armed groups – to play a role in the hostilities and engage in cyber operations that have the potential of harming civilians or damaging civilian infrastructure and that may amount to serious violations of IHL. Against this backdrop, this paper seeks to examine the legal grounds upon which hostile cyber operations carried out by non-State actors (NSAs) could constitute war crimes, thus entailing their individual criminal responsibility under international law. Hence, the analysis will focus on the applicability of the war crimes provisions of the Rome Statute of the International Criminal Court (ICC) to such operations, with a view to identifying the prerequisites necessary to trigger the ICC’s jurisdiction. To this end, the first part will focus on the increased involvement of NSAs in the conduct of hostilities by cyber means, taking the recent conflict between Russia and Ukraine as a pertinent case study. Subsequently, the paper will explore the conditions necessary for the application of Article 8 of the ICC Statute, with special attention devoted to those aspects that are deemed particularly problematic in light of the participation of NSAs in armed conflict. Finally, the paper seeks to highlight the limits of possible future investigations of cyber conducts possibly amounting to war crimes. These encompass not only issues of admissibility, but also the statutory limits of the Rome Statute when it comes to war crimes provisions applicable to noninternational armed conflicts.